3S’ Tourism Image and its Determining Factors: Evidence from North Cyprus - Maleki, Pegah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
This empirical study aims to investigate the effect of cognitive image of 3S tourism on attitude of tourist to 3S tourism activities. This research also examines the impact of attitude to 3S tourism of visit intention and word of mouth as two behavioral outcomes. Data were collected from tourists who travelled to North Cyprus in the summer 2015. The results revealed that image of 3S tourism had a positive relevance to tourist attitude. Visit intention and word of mouth are enhanced by improving visitors‘ attitude toward 3S tourism. There is a managerial implication with regard to the promotion of cognitive image in North Cyprus beaches, which results in positive outputs. Restrictions and prospective directions for future studies are discussed. Keywords: 3S Tourism, Cognitive Image, Attitude, Visit Intention, Word of Mouth, North Cyprus.

ÖZ Bu çalışmanın ana amacı zihinsel görüntünün etkilerini araştırarak 3 S Turizm faaliyetlerinde turistlerin davranışlarına göre 3 S turizm aktivitelerine yansımasını bulmak. Bu çalışma 3 S Turizminde davranışların etkisinin ziyaret niyeti üzerinde ve ağızdan ağıza iki davranış olarak çıktılarını incelemek. 2015 yılında yaz aylarında Kuzey kıbrıs‘ı ziyaret eden turistler ile ilgili veri toplamak.Bu sonuçlar göstermiştir ki 3 S Turizminin imajı pozitif olarak turist davranışları ile ilişkilidir. Ziyaret beklentisi ve ağızdan konuşmaların yapılması ziyaretçi sayısını artırarak 3 S turizimine yönelik bir tutum sağlamıştır. Kuzey Kıbrıs sahillerinin bilişsel imajını teşvik konusunda yönetsel bir içerik vardır. Bunun sonucunda da pozitif çıkışlarla sonuçlanır. Gelecekteki çalışmalarda sınırlamalar ve yön tartışılmıştır. Anahtar Kelimeler: 3S Turizimi, Bilşsel Görüntü, Davraniş, Ziyaret Beklentisi, Ağizdan Konuşma, Kuzey Kibris.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2015. Supervisor: Prof. Dr. Habib Alipour.
Keywords: Tourism; Tourism - Cyprus, North; 3S Tourism; Cognitive Image; Attitude; Visit Intention; Word of Mouth; North Cyprus